2014
DOI: 10.5897/ajb2014.13755
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol efficacy of Wickerhamomyces anomalus in moist maize storage

Abstract: White maiz without ino harvest and which high throughout decline in E hygiene. Th 2 months; n compared mycotoxin parameters uninoculate aspartic ac serine and poor surviv Key words: TRODUCTION ize is one of world. In Su th humans a ongs to the gal infection. cotoxins, not rage. Mycoto

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…W. anomalus was dominant in all silages at intermediate periods of fermentation, with a small participation of other genera. Other reports have shown that a mixed culture of selected yeasts and an LAB can be used as a biocontrol agent in silage to improve silage quality, because the mixed culture of yeasts could reduce the oxygen content and compete with the fungus for nutrition and space in the silage (Niba et al, 2014). However, regarding the fungal communities in silage fermentation, the data obtained from functional profiles of fungal communities are unclear and should be further validated through metabolomics.…”
Section: Discussionmentioning
confidence: 99%
“…W. anomalus was dominant in all silages at intermediate periods of fermentation, with a small participation of other genera. Other reports have shown that a mixed culture of selected yeasts and an LAB can be used as a biocontrol agent in silage to improve silage quality, because the mixed culture of yeasts could reduce the oxygen content and compete with the fungus for nutrition and space in the silage (Niba et al, 2014). However, regarding the fungal communities in silage fermentation, the data obtained from functional profiles of fungal communities are unclear and should be further validated through metabolomics.…”
Section: Discussionmentioning
confidence: 99%